Report of The Advisory Planning Board - Planning Commission (Planning Commission, 1946)
In Part IV of this report we put forward certain proposals for the future machinery of planning. These proposals really constitute our main recommendations for the general co-ordination and improvement of planning. In this Part, therefore, we shall simply view and make suggestions for the improvement of some of the individual branches of planning. We would like, however, first to refer to the "bottlenecks”, due to Jack of money, lack of capital equipment and raw materials, and lack of trained personnel, which may slow down the execution of development plans.
The Advisory Planning Board
The Advisory Planning Board